An earthquake-triggered submarine mass failure mechanism for the 1994 Mindoro tsunami in the Philippines: Constraints from numerical modeling and submarine geomorphology - Ramirez, Alec Benjamin G.; Ramos, Noelynna T.; Nawanao, Lyndon P.; Mangahas-Flores, Robelyn Z.; Narag, Ishmael C.; Baba, Toshitaka; Chikasada, Naotaka; Satake, Kenji (Frontiers in Earth Science, 2022)
Tsunamis have been known to result from a wide range of phenomena, such as earthquakes, volcanic eruptions, submarine mass failures, and meteorite impacts. Of earthquake-generated tsunamis, those arising from strike-slip mechanisms are less common, with the 1994 Mindoro tsunami in the Philippines among the few known examples. The 1994 Mindoro tsunami followed a Mw 7.1 earthquake along the right-lateral Aglubang River Fault. The tsunami affected the coasts surrounding the Verde Island Passage, one of the Philippines’ insular seas located between the islands of Luzon and Mindoro, and east of the West Philippine Sea margin. A total of 78 lives were lost due to the earthquake and tsunami, with 41 being directly attributed to the tsunami alone. Despite the close spatial and temporal association between the 1994 Mindoro earthquake and tsunami, previous numerical modeling suggests the need for other contributing mechanisms for the 1994 tsunami. In this study, we conducted submarine geomorphological mapping of the South Pass within the Verde Island Passage, with particular focus on identifying possible submarine mass failures. Identification of submarine features were based on Red Relief Image Map (RIMM), Topographic Position Index (TPI)-based landform classifaction, and profile and plan curvatures derived from high-resolution bathymetry data. Among the important submarine features mapped include the San Andres submarine mass failure (SASMF). The SASMF has an estimated volume of 0.0483 km3, and is located within the Malaylay Submarine Canyon System (MSCS) in the Verde Island Passage, ~1km offshore of San Andres in Baco, Oriental Mindoro. In this study, we explored two tsunami models (EQ-only and EQ+SMF) for the 1994 Mindoro tsunami using JAGURS. The source mechanisms for both models included an earthquake component based on the Mw 7.1 earthquake, while the EQ+SMF also included an additional, submarine mass failure component based on the San Andres SMF. Modeled wave heights from the EQ-only model drastically underestimates the observed wave heights for the 1994 Mindoro tsunami. In contrast, the EQ+SMF model tsunami wave height predictions were closer to the observed data. As such, we propose an earthquake-triggered, submarine mass failure source mechanism for the 1994 Mindoro tsunami.